2018
DOI: 10.32350/ibfr.2018.05.05
|View full text |Cite
|
Sign up to set email alerts
|

Islamic Banking Financing Effect on Growth

Abstract: The study is an attempt to explore the transmission channel through which development in Islamic banking could lead to economic growth. In order to determinethis transmission mechanism, the estimation based Vector Error Correction model (VECM) is used. This study has tested Murabaha, Ijarah and Diminishing Musharaka as proposed Islamic financial products because of their majority share in Islamic financing. This study has tested two co-integrated systems in the VECM model. The first system tests the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The results point towards the outcome that these Shariah-compliant products signifies their role in the economic growth process of Pakistan. The estimated results are in line with the findings of Mushtaq et al (2018), Kaleem et al (2016), Abduh and Omar (2012); Gudarzi and Sadr (2012) that came with the findings that these Shariah-compliant products have positive and significant effects on economic growth. Though most of the estimated coefficients are small in magnitude; however, the results showed that Shariah compliant financing has potential to boost-up the economy of Pakistan.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…The results point towards the outcome that these Shariah-compliant products signifies their role in the economic growth process of Pakistan. The estimated results are in line with the findings of Mushtaq et al (2018), Kaleem et al (2016), Abduh and Omar (2012); Gudarzi and Sadr (2012) that came with the findings that these Shariah-compliant products have positive and significant effects on economic growth. Though most of the estimated coefficients are small in magnitude; however, the results showed that Shariah compliant financing has potential to boost-up the economy of Pakistan.…”
Section: Resultssupporting
confidence: 89%
“…These results got confirmed in the later study of Haji (2018) who showed that Murabaha, Musharkah, Mudarbah and Ijarah were significantly and positively contributing to the GDP of Kenya. Mushtaq et al (2018) examined the transmission channel to assess whether development in Islamic banking does play any role in economic growth of Pakistan. Using the vector error correction model (VECM), they found that economic growth was positively related with Islamic banking products of Ijarah, Murabaha and DM.…”
Section: Pace Of Economic Growthmentioning
confidence: 99%
“…According to Jalil, Feridun, and Ma (2010), a single country analysis may provide a more appropriate framework for investigating the financegrowth nexus. Previous studies have used a single indicator, such as Islamic bank finance, Islamic banking assets, or Islamic banking deposits, to investigate the impact of Islamic financing on output growth (Abduh & Omar, 2012;Kalim, Mushtaq, & Arshed, 2016;Mushtaq, Arshed, & Kalim, 2018;Tabash & Dhankar, 2014). Since the sectoral composition of every economy is different (Asghar et al, 2021), so the financing needs may differ, so one financing type does not fit for all (Misman, Ahmad, Khairani, & Amran, 2020).…”
Section: Literature On Macroeconomic Variablesmentioning
confidence: 99%
“…A dearth of studies has inculcated Islamic equity/asset-backed or Islamic debt/asset-based financing in promoting entrepreneurship via risk-sharing or risk-mitigating mechanisms within the financial system. Several empirical studies have explored the role of Islamic financing on growth Kayed, 2012;Mushtaq et al, 2018), but its role in entrepreneurship is still underexplored. This study shows how Islamic debt-based contracts are useful for all prospective entrepreneurs and how this contract can decrease the access to finance gap for the entrepreneurs.…”
Section: Juristic and Asset-backed Financing As Motivating Factormentioning
confidence: 99%